2002
DOI: 10.1016/s0002-9440(10)64873-0
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor-165 Overexpression Stimulates Angiogenesis and Induces Cyst Formation and Macrophage Infiltration in Human Ovarian Cancer Xenografts

Abstract: Vascular endothelial growth factor (VEGF) is suggested to be an important regulator of angiogenesis in ovarian cancer. We have evaluated the effects of VEGF overexpression on the histology and growth rate of human ovarian cancer xenografts. OVCAR-3 human ovarian cancer cells were stably transfected with an expression vector encoding the 165-amino acid isoform of VEGF. As subcutaneous xenografts, moderately and highly VEGF(165)-overexpressing OVCAR-3 cells formed tumors with large cysts. Immunohistochemistry de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 33 publications
(39 reference statements)
0
33
1
Order By: Relevance
“…69, 70). As a consequence, tumor-associated monocytes/macrophages undergo marked phenotypic changes with activation of hypoxiainducible factor 1a, dramatically up-regulating the expression of a large number of genes encoding mitogenic, proangiogenic, and prometastatic cytokines, enzymes, and bioactive lipids (70,71). Interestingly, in vivo and in vitro studies have shown that VEGF, MMPs, and IL-6 in the tumor microenvironment inhibit the differentiation and maturation of dendritic cells and switch their differentiation toward the macrophage lineage (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…69, 70). As a consequence, tumor-associated monocytes/macrophages undergo marked phenotypic changes with activation of hypoxiainducible factor 1a, dramatically up-regulating the expression of a large number of genes encoding mitogenic, proangiogenic, and prometastatic cytokines, enzymes, and bioactive lipids (70,71). Interestingly, in vivo and in vitro studies have shown that VEGF, MMPs, and IL-6 in the tumor microenvironment inhibit the differentiation and maturation of dendritic cells and switch their differentiation toward the macrophage lineage (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of VEGF 165 overexpression on tumor progression in different tumor types is not entirely consistent. For example, overexpression of VEGF 165 enhanced both tumor angiogenesis and growth in a MCF-7 human breast carcinoma cell system (27) but only stimulated tumor angiogenesis without increasing the growth rate of OVCAR-3 human ovarian cancer xenografts (28). Varying degrees of effect were also noticed in preclinical models of h-cell carcinogenesis (29), melanoma (30), and glioma (31).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of the ␥-actin and VEGF 165 antisense probes have been described elsewhere (65). Hybridization to a 136-nt ␥-actin antisense probe gives rise to a protected fragment of 130 nt.…”
Section: Methodsmentioning
confidence: 99%
“…Hybridization to a 301-nt VEGF 165 antisense probe can give rise to fragments of different sizes due to protection by VEGF mRNAs of different isoforms. Hybridization of VEGF 165 mRNA results in the protection of a 252-nt fragment, whereas protection by VEGF 206 / VEGF 189 mRNAs or VEGF 145 /VEGF 121 mRNAs may give rise to protected fragments of 170 and 82 nt, respectively (65). As protection of the VEGF 165 antisense probe by VEGF 165 mRNAs is most efficient, effects on VEGF mRNA levels were monitored by assessing the mRNA levels of VEGF 165 .…”
Section: Methodsmentioning
confidence: 99%